2020
DOI: 10.1192/j.eurpsy.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between childhood trauma, cognitive biases, and cannabis use on the risk of psychosis in nonclinical young adults in Poland

Abstract: Background. Childhood traumatic events are risk factors for psychotic-like experiences (PLEs). However, the mechanisms explaining how trauma may contribute to the development of PLEs are not fully understood. In our study, we investigated whether cannabis use and cognitive biases mediate the relationship between early trauma and PLEs. Methods. A total sample of 6,772 young adults (age 26.6 ± 4.7, 2,181 male and 3,433 female) was recruited from the general population to participate in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
(96 reference statements)
1
23
0
Order By: Relevance
“…For the UHR population, a similar focus should be placed on the detection and treatment of risk factors and comorbidities to improve general health, well-being, and social and vocational functioning. Research indicates that the route from UHR to FEP is paved with interacting risk factors such as traumatic experiences, drug abuse (Belbasis et al, 2018), cognitive biases (Frydecka et al, 2020), worry, anxiety, insomnia and negative self-beliefs (Freeman, Taylor, Molodynski, & Waite, 2019) that may be effectively addressed with psychotherapy, which appears to improve resilience and the skills needed to cope with future problems. In psychotic disorders, recent studies have shown promising results in treating post-traumatic stress disorder (van den Berg et al, 2015), worry (Freeman, Dunn, et al, 2015), sleep disorder (Freeman, Waite, et al, 2015), and other causal risk factors in the development and maintenance of psychosis.…”
Section: Future Directionsmentioning
confidence: 99%
“…For the UHR population, a similar focus should be placed on the detection and treatment of risk factors and comorbidities to improve general health, well-being, and social and vocational functioning. Research indicates that the route from UHR to FEP is paved with interacting risk factors such as traumatic experiences, drug abuse (Belbasis et al, 2018), cognitive biases (Frydecka et al, 2020), worry, anxiety, insomnia and negative self-beliefs (Freeman, Taylor, Molodynski, & Waite, 2019) that may be effectively addressed with psychotherapy, which appears to improve resilience and the skills needed to cope with future problems. In psychotic disorders, recent studies have shown promising results in treating post-traumatic stress disorder (van den Berg et al, 2015), worry (Freeman, Dunn, et al, 2015), sleep disorder (Freeman, Waite, et al, 2015), and other causal risk factors in the development and maintenance of psychosis.…”
Section: Future Directionsmentioning
confidence: 99%
“…-a significant correlation between mPFC signal and verbal memory scores at posttraining in SCH-AT (r=0.51); no significant correlations at baseline nor in the SCH-CG group after intervention -no significant correlation between mPFC activity and executive functions at post-training -a significant correlation between the level of reality monitoring signal within the a priori spherical mPFC ROI immediately after training and ratings of social functioning at the 6 month follow-up (r=0.55) = 1.1) and also specifically identified more self-generated items (d = 1.01), with a trend effect for externally presented items (p = 0.07). The SCH-AT subjects, when compared to the HC subjects, identified the source of more word items overall at 16 -a significant main effect of group (d = 2.02); no significant interaction between mood and group, task accuracy and group, or between mood and task accuracy and group -between-group contrasts revealed HC performed significantly better than SCH at overall source-memory identification across both self-generated and externally presented word items (d = 0.87)…”
Section: Behavioral Results For Source Monitoringmentioning
confidence: 92%
“…It is then likely that several cognitive biases play a role in the etiology of psychotic symptoms. In line with cognitive approaches to psychosis [14,15] as well as with the observations that different factors may have additive effect on the risk of psychosis [16,17], different combinations of cognitive biases may also play a role. And yet, various cognitive biases are relatively rarely investigated simultaneously, despite that such studies could advance understanding of how these biases interact and how they lead to the development of psychotic symptoms in combination.…”
Section: Introductionmentioning
confidence: 93%
“…It is then likely that several cognitive biases play a role in the etiology of psychotic symptoms. In line with cognitive approaches to psychosis [14,15] as well as with the observations that different factors may have additive effect on the risk of psychosis [16,17], different combinations of cognitive biases may also play a role. And yet, various cognitive biases are relatively rarely investigated simultaneously, despite the fact that such studies could advance understanding of how these biases interact and how they lead to the development of psychotic symptoms in combination.…”
Section: Introductionmentioning
confidence: 82%